Optimization of loading consolidation and routing of vehicles from a cross-dock warehouse - Khoo, Wei Lun (2018)
Cross-docking is a process where goods from suppliers are delivered directly to the customers, with minimal storage and material handling through a cross-dock yard. It is a strategy widely used in the supply chain and logistics industry. This is to improve efficiency and productivity in the industry. In a cross-dock, minimal storage space is needed just for product consolidation as the goods do not stay there for long. However, for traditional warehouses, large amount of storage spaces is needed to keep the goods. They must wait until there is a customer order then it will be picked and delivered. Hence with cross-docking, it helps to reduce the total costs and increases customer satisfaction with a shorter delivery time. However, to achieve a good product flow in the cross-dock system, extensive use of planning software is needed. In this study, issues on the vehicle routing and the scheduling of the vehicles is considered. A mathematical model is proposed with the use of a meta-heuristic algorithm, Tabu search. In this study, the literature on the cross-dock operations is done first. It covers the problem faced on different operating levels. It then focuses on the vehicle routing and scheduling problem under the operational level. Followed by an extensive review on the model used with the incorporation of the Tabu search algorithm. The use of the aspiration criteria is also included in this study to allow better and attractive moves that are trapped in the restriction criteria to be overridden. Lastly, the results showed that despite having long computation time, an optimal route for the deliveries can be obtained which can minizine the total cost and lead to better customer satisfaction.